A Multidisciplinary Clinical Approach in Decision-Making in Complex Dento-Alveolar Trauma in the Maxillofacial Region: An Original Research - Abhilasha Patidar; Shruti Garg; Prasanti K. Pradhan; Priya Kumari; Anjali Raheja; Sitansu S. Das (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Dento-alveolar trauma impacts function and aesthetics, requiring a multidisciplinary approach involving oral surgeons, orthodontists, and prosthodontists. The lack of standardized protocols for complex cases results in fragmented care. Materials and Methods: A cross-sectional study was conducted with 500 dental professionals using a structured questionnaire to assess treatment preferences, interdisciplinary collaboration, and management practices. Data were analyzed using SPSS version 25. Results: Among participants, 60% prioritized surgical stabilization, 50% emphasized orthodontic alignment, and 40% focused on prosthodontic rehabilitation. A total of 70% recognized the importance of interdisciplinary collaboration. Multidisciplinary management improved functional and aesthetic outcomes. Conclusion: Collaboration among oral surgeons, orthodontists, and prosthodontists is crucial for optimal management of dentoalveolar trauma, enhancing patient outcomes.